The Disorientation of the Political Capacity of Indonesian Pro-Democracy Activists - Samadhi, Willy Purna (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
This study examines the political performance of pro-democracy activists in Indonesia after the end of the New Order. Using a democratic transformative politics approach, this study confronts aspects of the political capacity of pro-democracy activists with the need for popular control to work effectively. It finds that activists have been disoriented towards the development of political capacity and popular control. This study contributes to the study of Indonesian democracy by placing the issue of political capacity for building popular control as an integral part of the problem of democracy. The problems of democratisation are not only caused by the domination of political elites who have established oligarchies, but also by pro-democracy activists themselves ignoring the importance of developing collective political capacity as a means of advancing popular control. This study urges pro-democracy activists to re-orient their political capacity building and work with an agenda of consolidating the demos for civic democracy. Pro-democracy activists need to develop a systematic strategy of politicisation to strengthen citizens’ collective power through civic associations as a substitute forconstituents and voters.